ARTISTIC PSYCHOLOGISM IN THE NOVEL “JIMJITLIK” (TAMADDUN NURI JURNALI, 2025)
This article provides a literary-theoretical analysis of the artistic psychologism in Said Ahmad’s novel Jimjitlik. First, the general theoretical foundations of artistic psychologism are defined. Then, the depiction of characters’ inner states, mental struggles, inner monologues, and the creation of psychological portraits through artistic tools are examined. Thus, the psychological approach in Said Ahmad’s literary thinking is revealed.